Electrical wiring commercial - Mullin, Ray C. (Delmar, 1996)
Fully updated to reflect changes in the 1996 National Electrical Code, the 9th edition of this popular text provides a comprehensive, step-by-step approach to every phase of commercial wiring, from the simplest circuit to in-depth computations to determine service-entrance, branch-circuit, and feeder sizes. Students knowledge builds with each successive unit, working their way through a typical commercial building, and addressing many of the common issues of wiring installation, including commercial appliances and electrical equipment.. The new edition includes revised diagrams, text and review questions that reflect changes in the 1996 National Electrical Code. A comprehensive Metric Conversion chart has been added, and an expanded index locates topics either by alphabetical subject listing, or by 1996 NEC section number.. Loaded with examples, tables, wiring diagrams, illustrations, photographs, review questions, and a complete set of commercial floor and electrical plans, this unrivaled book ensures a solid and practical understanding of commercial electrical wiring.